Intuition as Philosophical Evidence - Pailos, Federico Matias (2012)
Earlenbaugh and Molyneux’s argument against considering intuitions as evidence has an uncharitable consequence — a substantial part of philosophical practice is not justified. A possible solution to this problem is to defend that philosophy must be descriptive metaphysics. But if this statement is rejected, one can only argue (a) that experts’ intuition does constitute evidence, and (b) that philosophical practice is justified by the overall growth of philosophical knowledge it generates.